The Effectiveness of Couple Therapy Model from the Perspective of Quran and Islamic Narrations on Family Efficiency and Jealousy of Couples - Jafari, Fateme; Pourshahriari, Mah Sima; Fayyaz, Fateme; Abdollahi, Abass (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The current research was conducted with the aim of the effectiveness of the couple therapy package of de-jealousy with an Islamic approach on family efficiency and jealousy in incompatible couples. Methods: The research method was experimental and within the framework of a quasi-experimental design of pre-test-post-test type with a control group with follow-up after two months. The statistical population of the present study included all couples in Tehran in 1400 who announced their readiness to participate in the training course for improving marital relations. After conducting the tests, the researcher selected the couples in which the women had a score lower than the average score in Safurai Parisi’s Family Efficiency Questionnaire (2008) and a score higher than the average score in the researcher’s Marital Jealousy Questionnaire and randomly placed them in the groups. 32 couples were selected from among the statistical population of the study by purposeful sampling and randomly replaced in two experimental and control groups. The participants of the educational group were subjected to the intervention of the couple therapy model from the perspective of the Qur’an and hadiths in 9 sessions of 90 minutes (Jaafari, Fayaz, Pourshahriari, and Abdulahi, 2021) and the control group did not receive any treatment. For data analysis, repeated measurement variance analysis was used with SPSS-25 statistical software. Results: The results of the analysis showed that the average scores of family efficiency in the experimental group compared to the control group increased (F=553.05, P=0.001) and the average scores of jealousy in the experimental group compared to the control group decreased (F=337/ 29, P=0.001). Conclusion: As a result, it can be said that the package of couples therapy to eliminate jealousy with an Islamic approach has been effective on family efficiency and jealousy in incompatible couples.